Nonconformity emerging through literature: a comparative analysis of A Portrait of the Artist as a Young Man and The Bell Jar - Jahan, Israt (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2024.